2014
DOI: 10.1080/09168451.2014.923291
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in mRNA expression of the serine-type carboxypeptidase ocpG in Aspergillus oryzae through intron retention

Abstract: (2014) Diversity in mRNA expression of the serine-type carboxypeptidase ocpG in Aspergillusoryzae through intron retention, Bioscience, Biotechnology, and Biochemistry, 78:8, 1328-1336,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…An increasing research has demonstrated that intron retention is widely found in animals, plants and fungi, serving as one of the effective strategies for post transcriptional regulation in eukaryotes [ 5 ]. In fungi, IR is reported to be involved in fungal cell complexity, pathogenicity [ 7 ], heat shock response [ 8 ], the nutrient sensing, such as glucose [ 9 ], and nitrogen source [ 10 ]. However, the function of IR in fungi has not been well studied, as compared to the extensive study of IR in animals and plants.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing research has demonstrated that intron retention is widely found in animals, plants and fungi, serving as one of the effective strategies for post transcriptional regulation in eukaryotes [ 5 ]. In fungi, IR is reported to be involved in fungal cell complexity, pathogenicity [ 7 ], heat shock response [ 8 ], the nutrient sensing, such as glucose [ 9 ], and nitrogen source [ 10 ]. However, the function of IR in fungi has not been well studied, as compared to the extensive study of IR in animals and plants.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing research has demonstrated that intron retention is widely found in animals, plants and fungi, serving as one of the effective strategies for post transcriptional regulation in eukaryotes [5]. In fungi, IR is reported to be involved in fungal cell complexity, pathogenicity [7], heat shock response [8], the nutrient sensing such as glucose [9], and nitrogen source [10]. However, the function of IR in fungi has not been well studied, as compared to the extensive study of IR in animals and plants.…”
Section: Introductionmentioning
confidence: 99%